Inhibition of Retrograde Transport Limits Polyomavirus Infection In Vivo - Saumya Maru (American Society for Microbiology, 2017)
ABSTRACT Polyomaviruses (PyVs) silently infect most humans, but they can cause life-threatening diseases in immunocompromised individuals. The JC polyomavirus (JCPyV) induces progressive multifocal leukoencephalopathy, a severe demyelinating disease in multiple sclerosis patients receiving immunomodulatory therapy, and BK polyomavirus (BKPyV)-associated nephropathy is a major cause of kidney allograft failure. No effective anti-PyV agents are available. Several compounds have been reported to possess anti-PyV activity in vitro, but none have shown efficacy in clinical trials. Productive PyV infection involves usurping the cellular retrograde vesicular transport pathway to enable endocytosed virions to navigate to the endoplasmic reticulum where virion uncoating begins. Compounds inhibiting this pathway have been shown to reduce infection by simian virus 40 (SV40), JCPyV, and BKPyV in tissue culture. In this study, we investigated the potential of Retro-2.1, a retrograde transport inhibitor, to limit infection by mouse polyomavirus (MuPyV) in vivo. We found that Retro-2.1 significantly reduced MuPyV levels in the kidney during acute infection without affecting renal function or the MuPyV-specific CD8 T cell response. To approximate the clinical setting of PyV resurgence in immunocompromised hosts, we showed that antibody-mediated depletion of T cells in persistently infected mice elevated MuPyV levels in the kidney and that Retro-2.1 blunted this increase in virus levels. In summary, these data indicate that inhibition of retrograde vesicular transport in vivo controls infection in a natural PyV mouse model and supports development of these compounds as potential therapeutic agents for individuals at risk for human PyV-associated diseases. IMPORTANCE PyVs can cause significant morbidity and mortality in immunocompromised individuals. No clinically efficacious anti-PyV therapeutic agents are available. A recently identified inhibitor of retrograde transport, Retro-2cycl, blocks movement of PyV virion-containing vesicles from early endosomes to the endoplasmic reticulum, an early step in the PyV life cycle. Retro-2cycl and its derivatives have been shown to inhibit infection by human PyVs in tissue culture. Here, we demonstrate that a derivative of Retro-2cycl, Retro-2.1, reduces infection by MuPyV in the kidneys of acutely infected mice. Mimicking the common clinical scenario of PyV resurgence, we further show that MuPyV levels increase in the kidneys of immunocompromised, persistently infected mice and that this increase is inhibited by Retro-2.1. These data provide the first evidence for control of a natural PyV infection in vivo by administration of an inhibitor of retrograde transport.